Is carbon lock-in blocking investments in the hydrogen economy? A survey of actors' strategies - Bento, N. (Energy Policy, 2010)
The difficulty of introducing hydrogen and fuel cells in the market stems from the fact that they are not an evolutionary innovation such as biofuels or hybrid cars. Instead they create a disruption in technological utilization. The domination of oil technologies sets a socio-economical context favoring actors involved in the current paradigm, and gives less opportunity to alternative fuels to develop and challenge the status quo. If this hypothesis is correct, then companies interested in the hydrogen economy would not become active because of an unstable context or contradictory interests concerning the replacement of the present system. A review of actions and announcements of main actors shows that technology readiness and the absence of infrastructure are the major justifications to delay investments. Some measures are discussed, which could be deployed in order to reduce uncertainties, such as regulation of carbon emissions from cars, technological subvention, and partnerships for infrastructure implementation.